HUBUNGAN PENDIDIKAN DENGAN PENGETAHUAN MASYARAKAT TENTANG STUNTING DI KOTA PADANG PANJANG - Yusti Siana; Rinita Amelia; Dian Puspita (Nusantara Hasana Berdikari, 2022)
Nutrition is the most important part in the growth and development of children. One of the nutritional problems suffered by toddlers is stunting. Stunting is a condition of failure to thrive in children under five years old (infants under 5 years old) as a result of chronic malnutrition which causes children to be too short for their age and brain function disturbances occur. Stunting conditions can be seen when the child is 2 years old. Short (stunted) and very short (severely stunted) toddlers are toddlers with body length (PB/U) or height (TB/U) that are in accordance with their age compared to the WHO-MGRS (Multicentre Growth Reference Study) standard. According to the Ministry of Health (Kemenkes), children under five with a Z-score score less than -2 SD/standard deviation (stunted) and less than -3 SD (severely stunted). Low nutritional intake is a direct cause of nutritional health problems in stunted children. Management of nutrition improvement is one way to reduce stunting rates, by focusing on food security, especially access to nutritious food, access to health services for treatment and prevention, and environmental health consisting of the availability of clean water and sanitation (environmental) facilities. These four factors affect the health status of mothers, children, and nutritional intake. The level of education of fathers and mothers is a strong factor in the incidence of stunting in children in Indonesia. Mother's knowledge and education is one of the important factors to prevent stunting in children.